Thermotropic, Thermo-morphologic, and Thermo-optical Properties of New Smectogenic Calamitic Compounds Containing Imine Linking Groups - Nesrullajev, Arif; Yorur-Goreci, Cigdem; Bilgin-Eran, Belkis (SPRINGER/PLENUM PUBLISHERS, 2012)
The synthesis and investigations of the mesomorphic, thermotropic, thermo-morphologic, and thermo-optical properties of two new salicylaldimine compounds, synthesized by our group, are reported in this work. Temperature transformations of specific textures of the smectic C mesophase, taking place in these compounds, and thermo-morphologic and thermotropic properties of the biphasic regions for direct and reverse phase transitions have been investigated. Temperature hysteresis and enlargement of the biphasic regions have been found. The character of texture transformations and temperature behavior of the optical birefringence indicate to the first order a smectic C-isotropic liquid-phase transition in these salicylaldimine compounds.
Keywords: Liquid crystals; Optical birefringence; Phase transitions; Salicylaldimine compounds; Thermotropic properties; PHASE-TRANSITIONS; LIQUID-CRYSTALS; COPPER(II) COMPLEXES; OPTICAL-PROPERTIES; LANDAU MODEL; BEHAVIOR; PECULIARITIES; DERIVATIVES; MESOPHASE; ALKOXY; Thermodynamics; Chemistry; Mechanics; Physics